Perbandingan Hasil Belajar Matematika Melalui Pembelajaran Kooperatif Tipe Number Head Together dan Student Team Achievement Division Pada Siswa MTs Muhammadiyah Penyasawan Kecamatan Kampar - Desi Anggraini (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This article aims to determine the differences in the results of learning mathematics by using the appropriate learning model in the application of cooperative learning model Number Head Type Togeteher (NHT) and Student Team Achievement Division (STAD) on the subject of Circles at MTs Muhammadiyah Penyasawan, Kampar District. In this research the problem statement is